Employee Retention Strategies of Hotel Industries in the Philippines Amidst the Pandemic - John Paul Galang; John Jay Pablo; Quennie Melad; Gemilu Ann Tamaray; Rizza Velasco; Karen Joy Catacutan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to determine the strategies of accredited hotel industries in retaining their employees amidst the pandemic in Tuguegarao City, Cagayan, Philippines. A quantitative research design employing descriptive research method was used in the study. The respondents of the study were the human resource manager or hotel owner of each accredited hotels in Tuguegarao City using a questionnaire. The findings of the study confirm that fourteen (14) strategies are fully employed in the five accredited hotels. However, the strategy concerning about the remuneration of employees even if there is a reduction in their total salary due to the limited working scheme set by the government is employed.